Selling the drama - Mohd Azmyl, Md Yusof * (The Malaysian Insight, 2023)
MIDWAY through my Azmyl & the Truly Asia US Tour about two weeks back, I made a cheeky post on my personal Facebook page about how a local mainstream press would prefer to cover a story (most probably syndicated) about a Singaporean band that was robbed while they were just at the start of their own US tour over an actual Malaysian band touring the US at the same time.